Sirolimus-coated balloon in all-comer population of coronary artery disease patients: the EASTBOURNE DIABETES prospective registry - Gianluca Caiazzo; Angelo Oliva; Luca Testa; Tay M. Heang; Chuey Y. Lee; Diego Milazzo; Giulio Stefanini; Nicola Pesenti; Antonio Mangieri; Antonio Colombo; Bernardo Cortese; on behalf of the EASTBOURNE investigators (Cardiovascular Diabetology, 2024)
Abstract Background The outcomes of percutaneous coronary intervention (PCI) in diabetic patients are still suboptimal, and it is unclear if diabetic patients might derive a benefit from the use of drug-coated balloons. Aims To evaluate the impact of diabetes mellitus on the outcomes of patients undergoing PCI with sirolimus-coated balloon (SCB) MagicTouch (Concept Medical, India). Methods We conducted a subgroup analysis of the prospective, multicenter, investigator-initiated EASTBOURNE registry, evaluating the performance of MagicTouch SCB in patients with and without diabetes. The study primary endpoint was target lesion revascularization (TLR) at 12-month follow-up. Secondary clinical endpoints were major adverse clinical events (MACE), death, myocardial infarction (MI), and BARC 2–5 bleedings. Results Among 2,083 enrolled patients, a total of 864 suffered from diabetes (41.5%). Patients with diabetes had a numerically higher occurrence of TLR (6.5% vs. 4.7% HR 1.38, 95%CI 0.91–2.08), all-cause death (3.8% vs. 2.6%, HR 1.81, 95%CI 0.95–3.46), and MACE (12.2% vs. 8.9%; HR 1.26 95%CI 0.92–1.74). The incidence of spontaneous MI was significantly higher among diabetic patients (3.4% vs. 1.5%, HR 2.15 95%CI 1.09–4.25); bleeding events did not significantly differ. The overall incidence of TLR was higher among in-stent restenosis (ISR) as compared to de-novo coronary lesions, irrespectively from diabetes status. Conclusions In the EASTBOURNE DIABETES registry, diabetic patients treated with the MagicTouch SCB did not have a significant increase in TLR when compared to non-diabetic patients; moreover, diabetic status did not affect the study device performance in terms of TLR, in both de-novo lesions and ISR.